Board Team Leadership Revisited: A Conceptual Model of Shared Leadership in the Boardroom - Vandewaerde, Maarten; Voordeckers, Wim; Lambrechts, Frank; Bammens, Yannick (2011)
In the slipstream of several large-scale corporate scandals, the board of directors has gained a pivotal position in the corporate governance debate. However, due to an overreliance on particular methodological (i.e. input–output studies) and theoretical (i.e. agency theory) research fortresses in past board research, academic knowledge concerning how this important governance mechanism actually operates and functions remains relatively limited. This theoretical paper aims to contribute to the promising stream of research which focuses on behavioural perspectives and processes within the corporate board, by delving into one of the research areas perhaps plagued most by these predominant approaches: board leadership. In adopting a team perspective on the board of directors our study goes beyond traditional board leadership research, which has turned a blind eye on actual leadership dynamics, by examining leadership processes and behaviours inside the board team. Specifically, we develop a conceptual framework addressing a novel and ethical approach to team leadership within the board, i.e. shared leadership, which has previously been demonstrated to result in performance benefits in various other team settings.
Keywords: Teams; SHARED leadership; Conceptual Framework; Board of directors; Board leadership